Atrial Fibrillation and Risk of ST-Segment–Elevation Versus Non–ST-Segment–Elevation Myocardial Infarction. Issue 21 (26th May 2015) - Soliman, Elsayed Z.; Lopez, Faye; O'Neal, Wesley T.; Chen, Lin Y.; Bengtson, Lindsay; Zhang, Zhu-Ming; Loehr, Laura; Cushman, Mary; Alonso, Alvaro
<x xml:space="preserve">Abstract</x> Background— It has recently been reported that atrial fibrillation (AF) is associated with an increased risk of myocardial infarction (MI). However, the mechanism underlying this association is currently unknown. Further study of the relationship of AF with the type of MI (ST-segment–elevation MI [STEMI] versus non–ST-segment–elevation MI [NSTEMI]) might shed light on the potential mechanisms. Methods and Results— We examined the association between AF and incident MI in 14 462 participants (mean age, 54 years; 56% women; 26% blacks) from the Atherosclerosis Risk in Communities (ARIC) study who were free of coronary heart disease at baseline (1987–1989) with follow-up through December 31, 2010. AF cases were identified from study visit ECGs and by review of hospital discharge records. Incident MI and its types were ascertained by an independent adjudication committee. Over a median follow-up of 21.6 years, 1374 MI events occurred (829 NSTEMIs, 249 STEMIs, 296 unclassifiable MIs). In a multivariable-adjusted model, AF (n=1545) as a time-varying variable was associated with a 63% increased risk of MI (hazard ratio, 1.63; 95% confidence interval, 1.32–2.02). However, AF was associated with NSTEMI (hazard ratio, 1.80; 95% confidence interval, 1.39–2.31) but not STEMI (hazard ratio, 0.49; 95% confidence interval, 0.18–1.34; P for hazard ratio comparison=0.004). Combining the unclassifiable MI group with either STEMI or NSTEMI did not change this conclusion. The association between AF and MI, total and NSTEMI, was stronger in women than in men (P for interaction <0.01 for both). Conclusions— AF is associated with an increased risk of incident MI, especially in women. However, this association is limited to NSTEMI.